2015
DOI: 10.1016/s2213-2600(15)00278-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of medically attended influenza during pandemic and post-pandemic seasons through the Influenza Incidence Surveillance Project, 2009–13

Abstract: Summary Background Since the introduction of pandemic influenza A (H1N1) to the USA in 2009, the Influenza Incidence Surveillance Project has monitored the burden of influenza in the outpatient setting through population-based surveillance. Methods From Oct 1, 2009, to July 31, 2013, outpatient clinics representing 13 health jurisdictions in the USA reported counts of influenza-like illness (fever including cough or sore throat) and all patient visits by age. During four years, staff at 104 unique clinics (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 21 publications
10
77
2
Order By: Relevance
“…We observed a higher burden of mild influenza for all ages groups in the 2014‐2015 season, dominated by the A(H3N2) influenza virus, when the annual cumulative influenza rate was estimated at 2367 ILI cases/100 000 population, the highest rate since the 2009 pandemic, suggesting a high transmissibility of the virus A(H3N2) during 2014‐2015 epidemic 20. In elderly individuals, our findings suggest a higher burden of mild cases in the 2011‐2012 and 2014‐2015 influenza seasons, dominated by A(H3N2), consistent with the high incidence of medically attended illness in this population previously reported by other authors in primary care during the same period 21. During the influenza seasons, where influenza B was predominant (2012‐2013 season) or presented at a late peak of activity (2014‐2015 and 2015‐2016 influenza seasons), we found that the 5‐14 age‐group was considerably more affected compared to other influenza seasons.…”
Section: Discussionsupporting
confidence: 91%
“…We observed a higher burden of mild influenza for all ages groups in the 2014‐2015 season, dominated by the A(H3N2) influenza virus, when the annual cumulative influenza rate was estimated at 2367 ILI cases/100 000 population, the highest rate since the 2009 pandemic, suggesting a high transmissibility of the virus A(H3N2) during 2014‐2015 epidemic 20. In elderly individuals, our findings suggest a higher burden of mild cases in the 2011‐2012 and 2014‐2015 influenza seasons, dominated by A(H3N2), consistent with the high incidence of medically attended illness in this population previously reported by other authors in primary care during the same period 21. During the influenza seasons, where influenza B was predominant (2012‐2013 season) or presented at a late peak of activity (2014‐2015 and 2015‐2016 influenza seasons), we found that the 5‐14 age‐group was considerably more affected compared to other influenza seasons.…”
Section: Discussionsupporting
confidence: 91%
“…Our estimates in these two age groups between the seasons 2002/03 and 2008/09 ranged from 2% to 17% (age group 0‐4; median 11%) and from 3% to 13% (age group 5‐14; median 8%), respectively, and are therefore comparable with the thoroughly conducted population‐based research study. Similarly, in the three seasons following the pandemic, influenza‐associated consultations by patients with ILI were estimated in a population‐based surveillance project in 13 US health jurisdictions as 0.7%, 0.2% and 1.1% 16. Given that only between 30% and 80% of all influenza cases manifest themselves as ILI5, 6, 7, 8 and in the same year influenza seasons may be quite different in different countries, the estimated 2.6%, 1.0% and 8.9% in our study lie in a comparable magnitude as the US data.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Influenza Incidence Surveillance Project (IISP) covering the 2009-10 through 2012-13 seasons revealed the highest rates of outpatient visits for influenza-positive ILI occurred among children aged 2 through 17 years (23). Complications, hospitalizations, and deaths from seasonal influenza are typically greatest among persons aged ≥65 years, children aged <5 years (and particularly those aged <2 years), and persons of any age who have medical conditions that confer increased risk for complications from influenza (1)(2)(3)(4)(24)(25)(26)(27)(28)(29).…”
Section: Burden Of Influenza Illnessmentioning
confidence: 99%